FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENERIMAAN ORANG TUA REMAJA PUTRI TERHADAP VAKSIN HUMAN PAPILLOMAVIRUS (HPV) - Nevin Zhasmin Miszka, (2023)
The problem in implementing cervical cancer prevention is related to parental acceptance. This study aims to determine the factors that influence the acceptance of parents of young women to the HPV vaccine in the Pejuang Health Center UPTD area. This research is a quantitative research with cross sectional research. The number of samples was 197 parents/guardians of young women with consecutive sampling in the Pejuang Health Center UPTD area. Data were analyzed by univariate, bivariate and multivariate analysis. The results of the chi square test showed that 3 variables had a significant relationship (p <0.05) with acceptance of the HPV vaccine with an odds ratio of knowledge (OR=3.01), attitude (OR=4.76), and health literacy (OR=2,15). The results of multivariate analysis showed that the most influential factor on acceptance of the HPV vaccine was attitude (OR=4.41). This shows that there is a relationship between knowledge, attitudes, and health literacy towards receiving the HPV vaccine in the parents of young women in the UPTD area of the Pejuang Health Center, with the influencing factor being attitude. Socialization efforts with social media in the future are needed to influence the attitudes of young women's parents.